2020
DOI: 10.1186/s12889-020-09969-8
|View full text |Cite
|
Sign up to set email alerts
|

Parental drinking according to parental composition and adolescent binge drinking: findings from a nationwide high school survey in Japan

Abstract: Background Alcohol problems in parents have been revealed to affect adolescent alcohol misuse. However, few studies examine the effects of parental drinking on adolescent risky drinking (including binge drinking) in the general population. In particular, previous study findings are inconsistent regarding the influence of parental drinking according to parental composition. In this study, we aimed to examine the relationship between parental drinking, according to parental composition, and binge drinking among … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
(123 reference statements)
1
7
0
Order By: Relevance
“…The 28 articles identified on parental alcohol intake only (i.e., not specifying children's observation of alcohol use) linked greater frequency and/or volume of consumption to negative alcohol‐related outcomes for their children [46, 79, 80, 83–107]. This effect was observed across numerous countries and cultural contexts, including Australia [87], Brazil [85, 90], Chile [86], China [105], Germany [97], Ireland [98], Japan [88], Mexico [107], Slovenia [96], Spain [101], Taiwan [79], the United Kingdom [91, 93, 94] and the United States [89, 92].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 28 articles identified on parental alcohol intake only (i.e., not specifying children's observation of alcohol use) linked greater frequency and/or volume of consumption to negative alcohol‐related outcomes for their children [46, 79, 80, 83–107]. This effect was observed across numerous countries and cultural contexts, including Australia [87], Brazil [85, 90], Chile [86], China [105], Germany [97], Ireland [98], Japan [88], Mexico [107], Slovenia [96], Spain [101], Taiwan [79], the United Kingdom [91, 93, 94] and the United States [89, 92].…”
Section: Resultsmentioning
confidence: 99%
“…The 28 articles identified on parental alcohol intake only (i.e., not specifying children's observation of alcohol use) linked greater frequency and/or volume of consumption to negative alcohol‐related outcomes for their children [46, 79, 80, 83–107]. This effect was observed across numerous countries and cultural contexts, including Australia [87], Brazil [85, 90], Chile [86], China [105], Germany [97], Ireland [98], Japan [88], Mexico [107], Slovenia [96], Spain [101], Taiwan [79], the United Kingdom [91, 93, 94] and the United States [89, 92]. Thirteen of the identified studies were longitudinal and found that parental alcohol use is associated with children subsequently engaging in underage alcohol consumption, suggesting a causal link between these two outcomes [79, 84, 87, 90–94, 97, 99, 101, 103, 104].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential sex differences were found in intergenerational relationships between parents and their offspring [ 15 , 16 ]. In this analysis, we paid special attention to the sex differences and found that boys’ SSB consumption was more susceptible to their parents' SSB intake than girls’, and fathers seemed to have a greater influence on whether children consume SSB than mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, prospective studies with a clearly defined temporal relationship are more convincing than cross-sectional studies in elucidating potentially causal links between family members’ SSB consumption and children’s SSB intake. Moreover, sex differences in intergenerational relationships between parents and offspring were found in alcohol consumption [ 15 ] and physical activity [ 16 ], and sex difference also exists in SSB drinking behavior [ 17 ]. These lead us to speculate on the possible sex differences in the association for SSB intake between parents and children, which did not attract widespread attention yet.…”
Section: Introductionmentioning
confidence: 99%